Current perspectives and trends of CD39-CD73-eAdo/A2aR research in tumor microenvironment: a bibliometric analysis - Huang, Tian; Ren, Xiangqing; Tang, Xiaolong; Wang, Yuping; Ji, Rui; Guo, Qinghong; Ma, Qian; Zheng, Ya; Hu, Zenan; Zhou, Yongning (Frontiers in Immunology, 2024)
Background and objective Extracellular adenosine (eAdo) bridges tumor metabolism and immune regulation. CD39-CD73-eAdo/A2aR axis regulates tumor microenvironment (TME) and immunotherapy response. In the era of immunotherapy, exploring the impact of the CD39-CD73-eAdo/A2aR axis on TME and developing targeted therapeutic drugs to enhance the efficacy of immunotherapy are the current research hotspots. This study summarizes and explores the research trends and hotspots of the adenosine axis in the field of TME to provide ideas for further in-depth research. Methods Literature information was obtained from the Web of Science core collection database. The VOS viewer and the bibliometric tool based on R were used to quantify and identify cooperation information and individual influence by analyzing the detailed information of the global annual publication volume, country/region and institution distribution, article authors and co-cited authors, and journal distribution of these articles. At the same time, the distribution of author keywords and the co-occurrence of author keywords, highly cited articles, and highly co-cited references of CD39-CD73-eAdo/A2aR in the field of TME were analyzed to determine research hotspots and trends. Result 1,721 articles published in the past ten years were included in this study. Through bibliometric analysis, we found that (1) 69 countries and regions explored the effect of the CD39-CD73-eAdo/A2aR on TME, and the research was generally on the rise. Researchers in the United States dominated research in this area, with the highest total citation rate. China had the most significant number of publications. (2) Harvard University has published the most articles in this field. (3) 12,065 authors contributed to the publication of papers in this field, of which 23 published at least eight papers. STAGG J had significant academic influence, with 24 published articles and 2,776 citations. Co-cited authors can be clustered into three categories. Stagg J, Allard B, Ohta A, and Antonioli, L occupied a central position in the network. (4) 579 scholarly journals have published articles in this field. The journal FRONTIERS IN IMMUNOLOGY published the most significant number of papers, with 97 articles and a total of 2,317 citations, and the number of publications increased year by year. (5) “The ectonucleotidases CD39 and CD73: Novel checkpoint inhibitor targets” was the most frequently local cited article (163 times). The “A2A adenosine receptor protects tumors from antitumor T cells” was the most co-cited reference (224 times). (6) Through the analysis of author keywords, we found that the relationship between adenosine and immunotherapy was a core concept for many researchers in this field. Breast cancer, melanoma, colorectal cancer, ovarian cancer, glioblastoma, pancreatic cancer, hepatocellular carcinoma, and lung cancer were the most frequent cancer types in adenosine-related tumor studies. Immunotherapy, immunosuppression, immune checkpoint, and immune checkpoint inhibitors were the hot keywords in the research, reflecting the importance of the adenosine metabolic pathway in tumor immunotherapy. The keywords such as Immunogenic cell death, T cells, Sting, regulatory T cells, innate immunity, and immune infiltration demonstrated the pathways by which adenosine affected the TME. The famous author keywords in recent years have been immunotherapy, immunogenic cell death, inflammation, lung cancer, and gastric cancer. Conclusion The effect of CD39-CD73-eAdo/A2aR on the infiltration and function of various immune cells in TME, tumor immunotherapy response, and patient prognosis has attracted the attention of researchers from many countries/regions. American scholars still dominate the research in this field, but Chinese scholars produce the most research results. The journal FRONTIERS IN IMMUNOLOGY has published the wealthiest research in the field. Stagg J was a highly influential researcher in this field. Further exploration of targeted inhibition of CD39-CD73-eAdo/A2aR alone or in combination with other immunotherapy, radiotherapy, and chemotherapy in treating various cancer types and developing effective clinical therapeutic drugs are continuous research hotspots in this field.